2004
DOI: 10.1128/iai.72.12.6836-6845.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of Swarming and Virulence by Fatty Acids through the RsbA Protein inProteus mirabilis

Abstract: After sensing external signals, Proteus mirabilis undergoes a multicellular behavior called swarming which is coordinately regulated with the expression of virulence factors. Here we report that exogenously added fatty acids could act as signals to regulate swarming in P. mirabilis. Specifically, while oleic acid enhanced swarming, some saturated fatty acids, such as lauric acid, myristic acid, palmitic acid, and stearic acid, inhibited swarming. We also found that expression of hemolysin, which has been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 42 publications
4
70
0
Order By: Relevance
“…Data of current research indicate that myristic acid and pantolactone may act as negative signals for regulation of bacterial virulence. Our finding supports the work of Liaw et al [41] who found that some saturated fatty acids inhibited swarming and virulence factor expression in Proteus mirabilis , Serratia marcescens , and Salmonella enterica . Hentzer et al [42] demonstrated that the Pseudomonas aeruginosa communication systems can be blocked by halogenated furanone compound.…”
Section: Resultssupporting
confidence: 93%
“…Data of current research indicate that myristic acid and pantolactone may act as negative signals for regulation of bacterial virulence. Our finding supports the work of Liaw et al [41] who found that some saturated fatty acids inhibited swarming and virulence factor expression in Proteus mirabilis , Serratia marcescens , and Salmonella enterica . Hentzer et al [42] demonstrated that the Pseudomonas aeruginosa communication systems can be blocked by halogenated furanone compound.…”
Section: Resultssupporting
confidence: 93%
“…Logically, regulators of the above biofilm factors, such as the RcsBCD phosphorelay (RcsD is also known as RsbA) (140, 177, 279) and RNA chaperone Hfq (164), control biofilm formation. Surface hydrophobicity, mediated by lipopolysaccharide (LPS) (53, 280, 281) and capsular polysaccharides (282–284), influence both initial surface colonization and biofilm maturation.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…During swarming, this mutant expresses higher levels of flagellin, as well as other swarming co-regulated virulence factors including hemolysin, protease, and urease (105). An RsbA-mediated pathway may involve sensing of saturated fatty acids to determine a tendency toward swarming or biofilm formation (107). That is, in the presence of specific fatty acids (myristic acid, lauric acid, palmitic acid), swarming behavior is inhibited while biofilm formation and extracellular polysaccharide production is enhanced.…”
Section: Two-component Systems That Regulate Flhdcmentioning
confidence: 99%